Knowledge and Adoption of Gram Production Technology (Indian Journal of Extension Education, 2011)
The study was conducted in Shahpura block of Jabalpur district (M.P.) to investigate the xtent of knowledge and adoption of gram production technology. There are thirteen blocks in Jabalpur district but Shahpura block has been selected purposively for the study because it covers largest area under gram cultivation as compared to other blocks. Ten villages were selected by using. SRSWOR (Simple Random sampling without replacement) for the study. Twelve gram growers from each village were randomly selected thus 120 gram growers were selected for the investigation purpose. The data were collected by using personal interview method. The collected data were tabulated, analyzed and interpreted with the help of appropriated statistical tools. The knowledge and adoption level of the gram growers were found moderate and low adoption level of recommended gram production technology respectively and there is significant association between knowledge level of gram growers and their adoption behavior.